Treatment of Latent Autoimmune Diabetes in Adults: What is Best? - Hals, Ingrid K. (Current Diabetes Reviews, 2019)
Latent Autoimmune Diabetes in Adults (LADA), although formally classified as Type 1 Diabetes (T1D), very often (at least in Western countries) appear clinically with Type 2 Diabetes (T2D)-like features as overweight and insulin resistance. LADA patients do not need exogenous insulin at the time they are diagnosed with diabetes, but a large percentage will within a few years develop need for such treatment. The decline in beta cell function progresses much faster in LADA than in T2D, presumably because of the ongoing autoimmune assault in LADA, and therefore necessitates insulin therapy much earlier in LADA than in T2D. Despite high prevalence of LADA (about 10% of the total diabetic population in many countries), the treatment of LADA patients is far less elucidated than is the case for T1D and T2D. Finding a treatment strategy for LADA from the time of diagnosis, that can reduce the decline of beta cell function, ensure adequate metabolic control and thereby reduce the risk of diabetic complications is thus an important clinical challenge. Conclusions from the randomized treatment studies so far do not indicate an optimal treatment strategy in LADA. This review aims to give an overview of current practices for the medical treatment of LADA as well as an update on results from recent studies on the treatment of the disease.
Keywords: GADA